(untitled) (World Bulletin of Public Health, 2022)
Joint (non-paralytic) strabismus (strabismus) is a condition in which one of the eyes permanently or intermittently deviates from the general fixation point, leading to impaired binocular vision in almost all patients. Binocular vision of the external world, impaired perception of movement and direction in space. Binocular vision can be detected in patients with strabismus only in 1–3% of cases [Avetisov E.S.]. As a rule, this condition is noted in cases where the eye has a small deflection angle and its long duration. With strabismus, visual acuity often causes the eye to squint. This condition is called dysbinocular amblyopia. Therefore, strabismus is not only a cosmetic defect but can also limit the patient’s professional capabilities. Strabismus in children and adults is both a psychophysical and a social problem, making it difficult to establish social connections